Hubungan Iklim Sekolah dengan Kepuasan Kerja Guru pada SD Negeri Kecamatan Padang Barat - Cici Yulia Safitri; Hadiyanto Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This research describes the correlation between school climate and job satisfaction in public elementary schools in Sub District of Padang Barat, Padang. The population of the research is 261 teachers, with a sample of 76 people by using cluster technique. The main instrument of this research is questionnaire using Likert scale model that had been tested for its validity and reliability. Based on the research, the school climate is in good category (79,74%) and the job satisfaction is in high category (85,79%). The results also showed the significant correlation between school climate and job satisfaction in public elementary schools in sub district of Padang Barat, Padang.